Evaluasi Efektivitas Sistem Informasi Akuntansi Berbasis Komputer Pada UMKM Di Kota Makassar: Pendekatan Model Delone & Mclean - Nasruddin Nasruddin; Rahmat Hidayatullah; Nur Asia; Aini Indrijawati; Syamsuddin Syamsuddin (Bata Ilyas Educational Management Review, 2026)
This study aims to evaluate the effectiveness of Computer-Based Accounting Information Systems (CBAIS) used by Micro, Small, and Medium Enterprises (MSMEs) in Makassar City, Indonesia. Drawing on the updated DeLone & McLean (2003) IS Success Model, this study examines the influence of system quality, information quality, and service quality on user satisfaction, and subsequently investigates the effect of user satisfaction on MSME performance. A quantitative survey approach was employed, with data collected from 150 MSME owners, managers, or finance staff who had utilized CBAIS for at least one year. Purposive sampling was applied, and data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Results indicate that all three quality dimensions significantly and positively affect user satisfaction (system quality: β = 0.390, t = 7.235, p < 0.001; information quality: β = 0.370, t = 7.538, p < 0.001; service quality: β = 0.203, t = 4.184, p < 0.001). User satisfaction, in turn, demonstrated a very strong and significant positive effect on MSME performance (β = 0.859, t = 50.571, p < 0.001). The novelty of this study lies in integrating technical, organizational, and user-outcome dimensions into a single comprehensive evaluation framework within the context of Indonesian MSMEs, providing empirical evidence on how CBAIS contributes to organizational performance improvement.